SELENIUM APPLICATION EFFECTS ON QUALITY AND DISTRIBUTION OF TRACE ELEMENTS IN SINK-SOURCE ORGANS OF WILD EMMER WHEAT - Y. Liang; Y. X. Chen; D. Q. Li; J. P. Cheng; G. Zhao; T. Fahima; J. Yan (Journal of Animal and Plant Sciences, 2020)
Mineral nutrient malnutrition, especially deﬁciency of selenium (Se) affects the health of approximately one billion people worldwide. Wild emmer wheat (Triticum turgidum ssp. dicoccoides), the progenitor of common wheat, harbors a rich genetic diversity for mineral nutrients. The study was conducted on two wild emmer wheat genotypes diﬀering in Se tolerance (R113, Se-sensitive; R171, Se-tolerant) with 2 Se application methods and 3 Se levels (foliar rates of 0, 11.5 and 23 mg.L-1; fertigation rates of 0, 5 and 10 mg.kg-1) in 2017 having 5 replications, at an experimental farm, Sichuan Province, China. It evaluated the effects of Se application on wild emmer wheat growth, grain yield and quality, and 14 other trace elements absorption and translocation in sink-source organs (flag leaves, husks and grains). The results showed that both foliar Se and fertigated Se application methods increased Se contents in sink-source organs, wheat health benefits and yield, while the foliar application was more effective than fertigation. Moreover, two Se application methods decreased toxic trace elements (Pb, Al, As, Li and Cd) contents in wheat, indicating a possible antagonistic effect. Accordingly, this study provided useful information concerning agronomic biofortiﬁcation of wheat, indicating that it is feasible to apply Se in fertilization programmes to inhibit the heavy metal elements contents and improve yield and quality in agricultural crops. The higher Se, Fe, Zn and Mo contents found in R171 suggested that its germplasm conferred higher abilities for mineral uptake and accumulation, which can be used for genetic studies of wheat nutritional value and for further improvement of domesticated cereals.
Keywords: Selenium; wild emmer wheat; genetic diversity; sink-source organs; yield and quality